2020
DOI: 10.1075/ml.20019.thw
|View full text |Cite
|
Sign up to set email alerts
|

Does verb transitivity influence word association responses?

Abstract: Although several studies have investigated the influence of the grammatical class of cue words on response patterns in the word association task, relatively little is known about the influence of more fine-grained distinctions such as cue transitivity. The present study test investigated two predictions of the influence of this variable made in existing studies. The first is that cue transitivity would influence the grammatical class of responses; the second, that it would affect the directionality of position… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The specific cues used in the study were the same as those used in a previous experiment investigating the influence of transitivity on word association responses (Thwaites, 2019(Thwaites, , 2020.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The specific cues used in the study were the same as those used in a previous experiment investigating the influence of transitivity on word association responses (Thwaites, 2019(Thwaites, , 2020.…”
Section: Methodsmentioning
confidence: 99%
“…That is, collocation lists for intransitive cues featured only words which preceded the cue in a corpus, and transitives only those words which followed the cue. This is because previous research has shown that intransitive cues yield significantly more responses which precede the cue than do transitives, while transitive cues are significantly more likely to yield responses which follow the cue (Thwaites, 2019(Thwaites, , 2020. After arriving at a list of collocates for each cue, the entropy of each collocational profile was calculated using…”
Section: Methodsmentioning
confidence: 99%